2016
DOI: 10.11648/j.ijnfs.20160504.20
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of Bacteria Isolates from Cabbage (<i>Brassica oleracea</i>), Carrots (<i>Daucus carota</i>) and Lettuce (<i>Lactuca sativa</i>) in the Kumasi Metropolis of Ghana

Abstract: Despite the benefits humanity derives from vegetables, they are as well a good source of foodborne illnesses when contaminated with pathogenic microorganisms especially the antibiotic resistant ones. This study evaluated the antibiotic resistance of bacteria isolated from three commonly consumed vegetables; cabbage (Brassica oleracea), carrots (Daucus carota) and lettuce (Lactuca sativa) in the Kumasi Metropolis in Ghana. The bacteria isolates were subjected to antimicrobial susceptibility testing using the Ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
2
1
0
Order By: Relevance
“…This agrees with the high E. coli counts reported in a similar study carried out on lettuce in Accra, although antibiotic resistance patterns were not assessed at that time [31]. Similarly, multidrug-resistant E. coli in lettuce was reported in two other studies from Kumasi and Tamale [24,25]. Moreover, the presence of ESBL-Ec isolates on the lettuce vegetables concurs with similar studies conducted in South Africa [41], Germany [42], the Netherlands [43] and Manilla [44].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This agrees with the high E. coli counts reported in a similar study carried out on lettuce in Accra, although antibiotic resistance patterns were not assessed at that time [31]. Similarly, multidrug-resistant E. coli in lettuce was reported in two other studies from Kumasi and Tamale [24,25]. Moreover, the presence of ESBL-Ec isolates on the lettuce vegetables concurs with similar studies conducted in South Africa [41], Germany [42], the Netherlands [43] and Manilla [44].…”
Section: Discussionsupporting
confidence: 87%
“…A PubMed search revealed a few studies on leafy vegetables from limited locations in Ghana, showing varying levels of bacterial contamination and antibiotic resistance [23][24][25][26]. However, only one study included an assessment of resistant genes [27].…”
Section: General Settingmentioning
confidence: 99%
“…However, another penicillin class of antibiotics, amikacin, two cephalosporins that are β-lactam agents (cefotaxime and ceftriaxone) and the only fluoroquinolone (ciprofloxacin) were highly sensitive against the isolated pathogens. As reported in this study, several other studies in Ghana and elsewhere have reported high prevalence of ampicillin, co-trimoxazole, tetracycline, gentamicin, cefuroxime, chloramphenicol, and meropenem resistant blood pathogens [46][47][48][49]. The resistance of blood pathogens to these antibiotics in this study could be associated with frequent use of these antibiotics in this setting.…”
Section: Plos Onesupporting
confidence: 71%